Outcome of Lung Functions in Covid-19 Patients at a Tertiary Care Center of Eastern Nepal - Koirala, Puru; Mehta, Ram Kumar; Koirala, Swastik Raj; Yadav, Gajendra Prasad; Parajuli, Surya B; Chaudhary, Santosh (Journal of Nobel Medical College, 2023)
Background: Novel coronavirus infection has myriad clinical manifestations, such as headache, respiratory failure, and long coronavirus disease syndrome. A common cause for admission is pneumonia, and such patients have shown longer periods of respiratory symptoms and exercise intolerance after discharge. The study aimed to determine short-term and long-term lung function outcomes in coronavirus disease patients. Materials and Methods: The prospective, cross-sectional study was conducted in coronavirus disease facility of Birat Medical College Teaching Hospital. A structured proforma including symptoms, modified medical research council dyspnea scale, 6-minute walk test and portable spirometry were recorded during 3 months follow up. Results: A total of 58 coronavirus disease patients were admitted, 4 expired. Common symptoms were dyspnea (98.28%), fever (94.8%), dry cough (86.2%), myalgia (17.2%). Mean Forced expiratory volume in 1 second to forced vital capacity ratio was normal. The mean forced vital capacity was 46.52% at admission, 53.33% at 3 months. The mean forced expiratory flow at 25% to 75% of forced vital capacity was 56.91% at admission, 59.31% at 3 months. Mean values of forced expiratory volume predicted was 47.40% at admission, 51.69% at 3 months. Mean 6-minute walk test distance did not improve during follow-up (240.09m at 1 month, 239.35m at 3 months) and there was no improvement in oxygen saturation at 3 months compared to the first month. Conclusion: Short-term lung function outcome demonstrated persistent dyspnea and development of mixed airways disease in all the survivors. Long-term lung function outcome observed was persistence of dyspnea, mixed airways disease, and low exercise capacity.